Pattern of Neck Node Metastases In Laryngeal Carcinoma - Saha, Bashudev Kumar; Fakir, Md Abu Yusuf; Islam, Mohammad Nazrul; Talukder, Debnath; Islam, Nazmul; Arefin, Mostafa Kamal (Journal of Dhaka Medical College, 2023)
Background: Cancer continues to be a major health problem despite advances in medical technology for its diagnosis and treatment. Cancer of the larynx is the eleventh most common cancer in the world. Carcinoma larynx is a multifactorial disease. Smoking, betel-nut, betel-leaf chewing habit and drinking alcohol are the most important factors associated with carcinoma larynx. Objective: To find out the patterns of neck node metastases in laryngeal carcinoma. Methods: Observational cross-sectional study was carried out in the Department of ENT and Head Neck Surgery, Dhaka Medical College Hospital (DMCH) from January’ 2018 to December’ 2019. Total 100 patients diagnosed as laryngeal carcinoma with neck metastases were included in this study. Statistical analyses were carried out by using the Statistical Package for Social Sciences version 23.0 for Windows (SPSS Inc., Chicago, Illinois, USA). Results: The mean age was found 57.8±12.7 years with range from 37 to 79 years. Males were predominant (76.0%) and females were (24.0%). Male: female ratio was 3.17:1. More than two third (68.0%) patients had supraglottis, 26.0% had glottis and 6.0% had subglottis. Supraglottic was found in 68 patients among them 27(39.7%) were T3, 18(26.5%) were T3. Glottic was found in 26 patients among them 16(61.5%) were T3, 6(23.1%) were T2, 4(15.4%) were T4a. Subglottic was found in 6 patients among them 4(66.7%) were T3 and 2(33.3%) was T2. Supraglottic was found in 68 patients among them 34(50.0%) were N1, 28(41.1%) were N2 and 6(8.8%) were N3. Glottic was found in 26 patients among them 20(76.9%) were N1 and 6(23.1%) were N2. Subglottic was found in 6 patients among them 4(66.7%) were N1 and 2(33.3%) was N2. supraglottic was found in 68 patients, among them majority 17(50.0%) patients were found in level II of neck nodes. Glottis was found in 26 patients, among them 16(61.5%) patients were found in level III of neck nodes. Subglottic found in 6 patients, among them 4(66.7%) patient was found in level IV of neck nodes. Unilateral neck node metastasis was more common 9(96.0%) than bilateral neck node metastasis 4(4.0%), out of them single neck node metastasis 84(84.0%) is more than multiple neck node metastasis 16(16.0%). Majority 46(46.0%) patients had stage III, 38(38.0%) had stage II, 10(10.0%) had stage I and 6(6.0%) had stage IV. Conclusion: Laryngeal carcinoma is a common clinical entity in otolaryngology practice. Male were more predominant and the highest age group was 51-60 years. Common clinical presentation was difficulty in swallowing and hoarseness of voice. In this study most common Laryngeal carcinoma was supraglottic in nature and majority of them were in level II. N1 was the most common pattern of neck node metastasis. Most of the neck nodes are unilateral and single. Stage III was the commonest stage of involvement. J Dhaka Med Coll. 2021; 29(1): 52-60